Fatty Acid Desaturase 1 Influences Hepatic Lipid Homeostasis by Modulating the PPARα‐FGF21 Axis - Shaminie Athinarayanan; Yang‐Yi Fan; Xiaokun Wang; Evelyn Callaway; Defeng Cai; Naga Chalasani; Robert S. Chapkin; Wanqing Liu (Hepatology Communications, 2021)
The fatty acid desaturase 1 (FADS1), also known as delta‐5 desaturase (D5D), is one of the rate‐limiting enzymes involved in the desaturation and elongation cascade of polyunsaturated fatty acids (PUFAs) to generate long‐chain PUFAs (LC‐PUFAs). Reduced function of D5D and decreased hepatic FADS1 expression, as well as low levels of LC‐PUFAs, were associated with nonalcoholic fatty liver disease. However, the causal role of D5D in hepatic lipid homeostasis remains unclear. In this study, we hypothesized that down‐regulation of FADS1 increases susceptibility to hepatic lipid accumulation. We used in vitro and in vivo models to test this hypothesis and to delineate the molecular mechanisms mediating the effect of reduced FADS1 function. Our study demonstrated that FADS1 knockdown significantly reduced cellular levels of LC‐PUFAs and increased lipid accumulation and lipid droplet formation in HepG2 cells. The lipid accumulation was associated with significant alterations in multiple pathways involved in lipid homeostasis, especially fatty acid oxidation. These effects were demonstrated to be mediated by the reduced function of the peroxisome proliferator–activated receptor alpha (PPARα)–fibroblast growth factor 21 (FGF21) axis, which can be reversed by treatment with docosahexaenoic acid, PPARα agonist, or FGF21. In vivo, FADS1‐knockout mice fed with high‐fat diet developed increased hepatic steatosis as compared with their wild‐type littermates. Molecular analyses of the mouse liver tissue largely corroborated the observations in vitro, especially along with reduced protein expression of PPARα and FGF21. Conclusion: Collectively, these results suggest that dysregulation in FADS1 alters liver lipid homeostasis in the liver by down‐regulating the PPARα‐FGF21 signaling axis.